Advanced characterization of coal microstructure before and after liquid nitrogen cold soaking - Shumin LIU; Xuelong LI; Dengke WANG (Meitan kexue jishu, 2023)
With the development of coal seam fracturing technology, promote the gas extraction by liquid nitrogen cold soaking fracturing coal has attracted widespread attention. In order to study the effect of liquid nitrogen cold soaking on the microstructures of different coals (lean coal, fat coal and anthracite) before and after liquid nitrogen cold soaking, the scanning electron microscopy (SEM), pore size distribution instrument and physical adsorption instrument were jointly characterized. The influence of liquid nitrogen cold soaking on the distribution of pore volume and specific surface area of different coal samples was comparatively analyzed. The results show that the thermal stress generated during the liquid nitrogen cold soaking destroys the microstructure of the coal or causes the initiation of micro-cracks, After liquid nitrogen cold soaking, the total pore volume and specific surface area of coal samples increase. The total pore volume growth rate of fat coal is the lowest, followed by anthracite, and the lean coal’s is the highest. The volume of micropores, micropores, meso-pores and macropores/fractures in the coal samples increase. cold leaching of liquid nitrogen causes macropores to pass through and form macropores/fissures in coal samples, resulting in the reduction of pore volume of macropores. After liquid nitrogen cold soaking, the pore specific surface area of each coal sample concentrate in the range of 10 − 100 nm, and has obvious peak characteristics. Liquid nitrogen cold soaking can increase the adsorption capacity of lean coal, fat coal and anthracite coal samples, and the adsorption capacity difference is the largest in the middle high pressure region (0.4 < p/p0 < 1.0). Liquid nitrogen cold soaking can effectively transform the internal microstructure of different coals. The research results are helpful to reveal the spatial expansion and connectivity of macroscopic and microscopic pore fractures in coal reservoirs during liquid nitrogen cracking.